Toward Predicting Prosocial Behavior: Music Preference and Empathy Differences Between Adolescents and Adults - Clark, Shannon Scott; Giacomantonio, S. Giac (Empirical Musicology Review, 2015)
Empathy plays a role in social competence and intelligence, and can serve as a buffer against antisocial tendencies. Numerous studies highlight the relationship between empathy, prosocial behaviors, and the predictive utility of music preferences. This study examined participant differences in music preferences and empathy as a function of age, and whether preferred music genre predicted empathy (as a correlate to prosocial behavior). A new measure was devised to assess music preferences more accurately (i.e. with better face/construct validity) than existing measures. The Basic Empathy Scale measured empathy as a multidimensional construct. Younger participants exhibited greater empathy than older ones. Each music preference factor contributed uniquely to empathy variance in multiple regression models. Younger and older participants differed on music preferences (arguably associated with age-related sociocultural influences). Conclusions were drawn regarding the age differences in empathy and music preferences, the systematically greater influences of music preferences on cognitive compared to affective empathy, and the greater associations with empathy of specific music preferences. Limitations and implications for government policy and further research are discussed.